HELIUM ISOTOPIC COMPOSITION OF HYDROTHERMAL FLUIDS FROM THE MANUS BACK-ARC BASIN, PAPUA NEW GUINEA - Fourre E.; Jean-Baptiste P.; Charlou J.-L.; Donval J.P.; Ishibashi J.I. (My University, 2006)
We present isotopic analysis of helium in hydrothermal fluids from the Manus back-arc basin, collected during the French-Japanese Manusflux and Manaute cruises in 1995 and 2000, respectively. The helium isotope composition of the fluids is comparable to that measured elsewhere in similar subduction environments, with 3He/4He values (7.4 to 7.9 Ra) slightly lower than typical MORB values, except on the Manus Spreading Center (MSC) where higher values (12 ± 0.1 Ra) are observed. The causal link between the narrow spatial extent of the 3He/4He anomaly at the MSC and a 3He-rich deep mantle component remains elusive, based on available geophysical data. Thus, the Manus Spreading Center results may be an interesting example of small scale upper-mantle heterogeneity. Copyright © 2006 by The Geochemical Society of Japan.
Keywords: BACK-ARC BASINS; HELIUM ISOTOPES; HYDROTHERMAL FLUIDS; MANUS BASIN; WESTERN PACIFIC